PERANAN TENTANG NILAI GOTONG ROYONG SEBAGAI BENTUK PENERAPAN SILA KE-TIGA PANCASILA DI DESA WONOREJO KECAMATAN BANYUPUTIH KAB. SITUBONDO - Bayu Indra Permana; Agus Mursidi (Universitas PGRI Madiun, 2020)
Mutual cooperation is a social activity and a characteristic of the Indonesian people. As stated in Pancasila, the third principle is